The Arabic Language in Social Medias’ era - Salaah Rashid, Huda (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article aims to identify the challenges that are facing Arab countries to establish their language in the information society and social networks in particular. An attempt was made to identify the impact of the digital world on the language, followed by a statistical analysis approach. The type of study merits an analysis of reality data extrapolating the use of the Arabic language and its levels among diverse groups with multiple cultures and age stages distributed between less than 18-65 years.